Protein analysis and gene expression indicate differential vulnerability of Iberian fish species under a climate change scenario - Jesus, Tiago Filipe (2017)
Current knowledge on the biological responses of freshwater fish under projected scenarios of climate change remains limited. Here, we examine differences in the protein configuration of two endemic Iberian freshwater fish species, Squalius carolitertii and the critically endangered S. torgalensis that inhabit in the Atlantic-type northern and in the Mediterranean-type southwestern regions, respectively. We performed protein structure modeling of fourteen genes linked to protein folding, energy metabolism, circadian rhythms and immune responses. Structural differences in proteins between the two species were found for HSC70, FKBP52, HIF1α and GPB1. For S. torgalensis, besides structural differences, we found higher thermostability for two proteins (HSP90 and GBP1), which can be advantageous in a warmer environment. Additionally, we investigated how these species might respond to projected scenarios of 3 climate change warming, acidification (ΔpH = -0.4), and their combined effects. Significant changes in gene expression were observed in response to all treatments, particularly under the combined warming and acidification. While S. carolitertii presented changes in gene expression for multiple proteins related to folding (hsp90aa1, hsc70, fkbp4 and stip1), only one such gene was altered in S. torgalensis (stip1). However, S. torgalensis showed a greater capacity for energy production under both the acidification and combined scenarios by increasing cs gene expression and maintaining ldha gene expression in muscle. Overall, these findings suggest that S. torgalensis is better prepared to cope with projected climate change. Worryingly, under the simulated scenarios, disturbances to circadian rhythm and immune system genes (cry1aa, per1a and gbp1) raise concerns for the persistence of both species, highlighting the need to consider multi-stressor effects when evaluating climate change impacts upon fish. This work also highlights that assessments of the potential of endangered freshwater species to cope with environmental change are crucial to help decision-makers adopt future conservation strategies. © 2017 Jesus et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.